Post‐industrial urban shrinkage in Lisbon: planning challenges for former manufacturing sites - Vale, Mário (2018)
The paper aims are twofold: This paper develops a new approach to measure physical change outcomes of urban shrinkage (No Void project). The paper showcases Lisbon city, which has suffered depopulation, explained by economic restructuring, and suburbanization and the effects of economic cycles (boom and bust) mingled with political options, comparing two manufacturing areas (East and Southwest) with different fortunes.